COVID-19 related disruption in higher education students' health and wellbeing: Implications for university action - Stock, Christiane; Helmer, Stefanie M.; Heinrichs, Katherina (Frontiers in Public Health, 2022)
The COVID 19 pandemic has led to substantial disruptions in the lives of students in higher education. Partial or full closures of institutions for face-to-face teaching or consultations over a long-lasting period of time in many countries have had significant consequences on the psychosocial health and wellbeing of many students. This perspectives article summarizes the implications on mental, social, and behavioral aspects of students' wellbeing. Moreover, the need for health promoting und supportive services, programmes, structures, and policies is outlined with recommendations for institutional actions on the level of teaching practice, counseling services, and health monitoring, and with the call to re-affirm the wider policy-oriented approach of the Health Promoting University.